Exploring Apprenciative Pedagogic Classroom Practices of the Secondary Level Teachers - Pokhrel, Tika Ram; Shrestha, Tej Krishna (ILAM इलम, 2026)
Appreciative Inquiry (AI) reflects the overall practices of a school. The teachers and students enjoy the teaching-learning environment where there is the use of an AI approach. The practices of teachers in their classrooms are expected by the principles of AI. The purpose of the study is to explore the classroom practices of teachers related to AI. A qualitative research method was used to explore the practices of AI in two schools in Bhaktapur district, Nepal. Interviews with teachers and students and observation of classrooms were the tools of data collection used in the study. The findings show that students are highly motivated by the intrinsic and extrinsic motivation that the teachers provide during teaching and learning. Teachers seek some additional training from the administration so that they can update their knowledge and skills. Teachers’ AI practices are different from the nature of the subjects. Students feel more comfortable with the teachers of soft subjects (for example, Social Studies) than with the teachers of hard subjects (for example, Math teachers). It helps the students learn better and encourages the teachers to teach effectively and create an appropriate learning environment in the classroom.